An effective protocol for callus induction with milk clotting activity from solanum dubiumSeeds - Fatima Musbah Abbas,; ElBushra ElSheikh ElNur,; Normah Mohd Noor Eisa Algaali,; Zainon Mohd Ali,; Roohaida Othman, (Universiti Kebangsaan Malaysia, 2011)
The aim of this study was to establish an effective protocol for callus induction from the seed explants of Solanum dubium and to investigate the callus extract ability in milk clotting activity. The effects of growth regulator, basal media strength and sucrose were studied using different concentrations (0.5, 1.0, 1.5, and 2.0 mg/L) of indole-3-acetic acid (IAA), indole-3-butyric acid (IBA), naphthalene acetic acid (NAA) and 2,4-dichlorophenoxy-acetic acid (2,4-D) alone or in combination with 0.5 mg/L of 6-benzylamino purine (BAP). For milk clotting activity, about 50 or 100 μL extracts of seed callus was mixed with 2 mL 50% milk held at 55°C for 5 and 10 min until milk clotting occurred. The results showed that NAA alone or in combination with BAP gave a higher callusing percentage (80 to100%) compared to the other plant growth regulators at the same concentrations. When an auxin was supplied in combination with BAP, a significant increase in callusing percentage or degree of callusing was observed. The time required for callus to be developed was shortened and the quality of the induced callus improved. An increase in callus growth in low sucrose (10 g/L) concentration was found be comparable (88%) to high sucrose concentration (30 g/L; 60%). Crude extracts obtained from S. dubium callus were shown to exhibit milk clotting activity.